Vaginal bleeding in pregnancy and adverse clinical outcomes: a systematic review and meta-analysis - Arezoo Karimi; Kourosh Sayehmiri; Mojtaba Vaismoradi; Mostafa Dianatinasab; Salman Daliri (Journal of Obstetrics and Gynaecology)
Background Vaginal bleeding during pregnancy has been recognised as a significant risk factor for adverse pregnancy outcomes. This study aimed to investigate the association between vaginal bleeding during the first trimester of pregnancy and clinical adverse effects using a systematic review and meta-analysis.Methods Databases of Scopus, Web of Science, PubMed (including Medline), Cochrane Library and Science Direct were searched until June of 2023. Data analysis using statistical test fixed- and random-effects models in the meta-analysis, Cochran and meta-regression. The quality of the eligible studies was assessed by using the Newcastle–Ottawa Scale checklist (NOS).Results A total of 46 relevant studies, with a sample size of 1,554,141 were entered into the meta-analysis. Vaginal bleeding during the first trimester of pregnancy increases the risk of preterm birth (OR: 1.8, CI 95%: 1.6–2.0), low birth weight (LBW; OR: 2.0, CI 95%: 1.5–2.6), premature rupture of membranes (PROMs; OR: 2.3, CI 95%: 1.8–3.0), abortion (OR: 4.3, CI 95%: 2.0–9.0), stillbirth (OR: 2.5, CI 95%: 1.2–5.0), placental abruption (OR: 2.2, CI 95%: 1.4–3.3) and placenta previa (OR: 1.9, CI 95%: 1.5–2.4).Conclusions Vaginal bleeding in the first trimester of pregnancy is associated with preterm birth, LBW, PROMs, miscarriage, stillbirth, placental abruption and placenta previa. Therefore, physicians or midwives need to be aware of the possibility of these consequences and manage them when they occur.